The Implementation of Marketing Mix to Increase Room Sales - Wahyuntari, Ni Luh Putu; Sutarma, I Gusti Putu; Antara, Dewa Made Suria (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
This research aims to determine the effect of the implementation of the marketing mix consisting of product strategy are, price strategy promotion strategy, place strategy, process strategy, person strategy, and physical evidence strategy for increasing the room sales at a 4-star hotel in Kuta, Badung. To answer the existing problems needed supporting statistics obtained through observation, interviews, and documentation. Based on the result of the implementation of marketing mix strategies, it was obtained significantly an increase in the room sales. The marketing mix factors are; product strategy, by the product strategy hotel management able to increase the room sales in accordance with occurring the guest needed; Price strategy, it’s about strategy to establish the right prices in market segmentation; Promotion strategy, this strategy is consolidating the technical of marketing through promotion by social media, electronics promotions, and any publics publishing; Place strategy consist with classify the distribution channels. People’s strategy, this strategy advise some strategies for developing training that can improve work performance; physical evidence strategy, advise the strategy of revamping the hotel facilities and infrastructure of the hotel.